Research on Active-passive Joint Support Technology for the Roadway of Thick Coal Seam Mining - Zhang, Linchao; Huang, Yingjun; Ren, Dahua; Wei, Sijiang (International Journal of Natural Resources and Environmental Studies, 2024)
The lower trench of 2301 working face of Anyang Main Coking Coal Mine has the problems of large deformation of surrounding rock and high difficulty of maintenance in the process of digging. According to the deformation characteristics of the surrounding rock, a "U-type steel + anchor cable" joint support technology is proposed to control the deformation. In this paper, the main parameters of joint support are studied through numerical simulation, and the effect of perimeter rock control is verified through on-site monitoring. The results show that: within a reasonable range of preload force, the larger the preload force of the anchor cable, the better the effect of controlling the deformation of the surrounding rock; when the bracket row spacing is 600-800mm, the stability of the surrounding rock of the roadway can be ensured; during the roadway excavation, the maximum deformation of the surrounding rock is 40mm, which realizes the control of the stability of the surrounding rock in the roadway of the top coal of the soft and thick coal seam.